Le Calvaire - Mirbeau, Octave, 1848-1917 (Salt Lake City, UT : Project Gutenberg, 2013)
"Le Calvaire" by Octave Mirbeau is a novel published in 1886. This largely autobiographical work follows Jean Mintie, a writer with literary potential who becomes consumed by sexual obsession. Entrapped by a woman of questionable morals, he descends into humiliation and impotence, struggling to transform his suffering into creative fuel. His redemptive passion mirrors the Passion of Christ, though the novel ultimately reveals a darker vision of love as battlefield and its casualties as fallen martyrs. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Le_Calvaire
Release date is 2013-11-09
Produced by Madeleine Fournier and Marc D'Hooghe (From images generously made available by the Internet Archive)
Keywords: France -- Social life and customs -- 19th century -- Fiction